Targeting Myeloid Checkpoint Molecules in Combination With Antibody Therapy: A Novel Anti-Cancer Strategy With IgA Antibodies? - Chan, Chilam; Lustig, Marta; Baumann, Niklas; Valerius, Thomas; van Tetering, Geert; Leusen, Jeanette H. W. (Frontiers in Immunology, 2022)
Immunotherapy with therapeutic antibodies has shown a lack of durable responses in some patients due to resistance mechanisms. Checkpoint molecules expressed by tumor cells have a deleterious impact on clinical responses to therapeutic antibodies. Myeloid checkpoints, which negatively regulate macrophage and neutrophil anti-tumor responses, are a novel type of checkpoint molecule. Myeloid checkpoint inhibition is currently being studied in combination with IgG-based immunotherapy. In contrast, the combination with IgA-based treatment has received minimal attention. IgA antibodies have been demonstrated to more effectively attract and activate neutrophils than their IgG counterparts. Therefore, myeloid checkpoint inhibition could be an interesting addition to IgA treatment and has the potential to significantly enhance IgA therapy.